An Africentric theory of human personhood - Nwoye, Augustine (PINS-Psychology in Society, 2017)
The principal objective of this article is to work out an Africentric theory of human personhood. The aim is to attempt an African psychological rendering of that fundamental African assumption, made popular by the Nguni proverb, that “umuntu ngumuntu ngabantu” (often translated as “a person is a person through other persons”). To achieve this aim an African psychological theory of human personhood is offered to demonstrate that, in Africa as in other parts of the world, mature human beings are not born but made. In grounding the theory within an Africentric paradigm, the following themes that reflect an African origin of the theory are discussed: the basic postulates of an African worldview; an Africentric theory of human motivation; influential agents, moral visions, and social processes in the formation of an African personhood. The central goal of the discussion is to show how African personhood is socio-culturally derived and to point at the variety of enduring forces, both ancient and modern, determining its distinctive form.